Chronic toxicity of uranium to three benthic organisms in laboratory spiked sediment. (January 2022) - Simon, Olivier; Coppin, Frederic; Micozzi, Nadine; Beaugelin-Seiller, Karine; Février, Laureline; Henner, Pascale; Della-Vedova, Claire; Camilleri, Virginie; Gilbin, Rodolphe
Abstract: Due to mining activities, concentration of uranium (U) in the environment nearby former and operating sites can be higher than in other areas. The derivation of quality criteria for U in freshwater ecosystems, rivers and lakes includes the consideration of contaminated sediments and the associated risk to the benthic life. Therefore, the derivation of a quality criteria for sediment has been viewed as a logical and necessary extension of the work already done to establish water quality criteria. In order to contribute to the determination of a Quality Standard for sediment (QSsediment ) according to the European recommendations, this study focuses on the acquisition of a new toxicity dataset, to enrich the few rare existing data, most often unsuitable. A basic set of organisms, including three complementary benthic organisms ( Chironomus riparius, Hyalella azteca, Myriophyllum aquaticum ), was chronically exposed to U spiked to a standard laboratory-formulated sediment, according to the related bioassay guidelines (ISO/FDIS16303, OECD 218/9, ISO/DIS 16191). We looked to determine when possible both NOEC and EC10 values for each organism. For C. riparius, a NOEC (emergence rate) value was estimated at 62 mgU, kg −1, dm and the EC10 value reached 188 mgU, kg −1, dm (CI95% 40–885 mgU kg −1, dm). For H. azteca, a NOEC (survival rate) value of 40 mgU kg −1, dm was observed while the EC10 value at 296 mgU kg −1, dm (CI95%  = 155–436 mgU kg −1, dm) was slightly higher than for growth at 199 mgU kg −1, dm (CI95%  = 107–291 mgU kg −1 dm). Finally, the less sensitive organism seemed to be the plant, M. aquaticum, for which we determined a NOEC value of 100 mgU kg −1, dm. Results obtained regarding the toxicity of U made it possible to suggest a preliminary QSsediment value of 4 mgU kg −1, dry mass. This value was shown conservative compared to U sediment quality criteria derived by other jurisdictions. Highlights: Toxicity of U spiked artificial sediment was assessed according to standardized bioassays for 3 benthic species. Survival rate of H. azteca led to a preliminary Quality Standard value derivation of 4 mgU kg −1, dry mass. The derived preliminary Quality Standard was shown conservative compared to the reported toxicity of U in natural sediments.